A Sector-Wide Data Collection Framework for Improving Operational Efficiency in Nigeria’s Retail Logistics Ecosystem - Opeyemi Morenike Filani,; John Oluwaseun Olajide,; Grace Omotunde Osho, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Nigeria's retail logistics ecosystem faces challenges stemming from infrastructural deficits, fragmented supply chain practices, and limited real-time data availability, leading to inefficiencies in operational planning and execution. This paper proposes a sector-wide data collection framework to enhance operational efficiency within Nigeria's retail logistics by leveraging digital tools and collaborative data-sharing models. Grounded in a systematic literature review, the study identifies existing gaps in data management practices, the role of data in enabling predictive logistics, and the benefits of sectoral collaboration in overcoming systemic inefficiencies. The proposed framework integrates IoT-enabled data capture, standardized data protocols, and a shared digital platform to facilitate real-time visibility, optimize routing and inventory decisions, and support sustainable logistics practices across the Nigerian retail sector. This framework serves as a blueprint for stakeholders aiming to align with digital transformation goals, enhance service delivery, and drive down operational costs within the context of Nigeria's dynamic and evolving retail landscape.
Keywords: data collection; operational efficiency; Nigeria retail logistics; sector-wide framework; supply chain visibility; digital transformation